Retirement Village Design Features : Generation X’s Expectation - Asmah Alia, Mohamad Bohari; Farah Ajlaa, Julaihi; Kuryati, Kipli; Mohd Azrai, Azman; Sharifah Rahama, Amirul; Xin, Hu (UPM Press, 2024)
The retirement village is increasingly accepted as a suitable living arrangement for older people post-retirement. Nevertheless, the specific design elements that should be included in the village to cater for the needs of elderly individuals in Malaysia remain unclear and open to interpretation. Thus, this research examines Generation X’s expectations of the required features that a retirement village should have for more sustainable living. Generation X is selected as the case study as this generation will be the nearest generation that will be the occupant of the retirement village. In this quantitative study, the questionnaire survey method is utilised to investigate the correlation between two primary concepts: the design feature of retirement villages and their influence on the motivation to relocate to such communities. The factors are identified from the integrative literature review conducted. The structural equation model is used to verify if the retirement village design features can significantly influence Generation X’s motivation to move into a retirement village in Malaysia. The retirement village posed three important design features: senior oriented basic settings, age-friendly social environment, and environmentally friendly design features. The outcome could guide stakeholders to view the retirement village concept based on the local context and set the stage for future research on age-friendly housing facilities for older individuals. However, the results derived from this paper are purely based on the quantitative approach and can be further validated through a qualitative approach to understand each outcome better.